An Efficient One Pot Multicomponent Synthesis of Dihydro Pyrazolyl Bisthiazole Derivatives as Potential Anticancer Agents and their Molecular Docking Studies - Varluvothu, Anjaneyulu; Vaarla, Krishnaiah; Kumar Kesharwani, Rajesh; Leelavathi, Panaganti (Asian Journal of Chemistry, 2022)
A novel series of dihydropyrazolyl bisthiazoles were synthesized through simple reaction conditions via one pot multicomponent reaction of 2-bromo-1-(4-methyl-2-phenyl thiazol-5-yl)ethan-1-one, thiosemicarbazide and chalcones in the presence of sodium hydroxide in ethanol under reflux condition. The reaction generates two potential five membered heterocylic pharmacophores i.e. Hantzsch thiazole and dihydropyrazole in one step through simple operation, in shorter reaction time with high yields. The newly synthesized compounds were well characterized by IR, 1H, 13C NMR and mass spectral data. All the newly synthesized compounds were evaluated for their anticancer activity against human cancer cell lines and calculated their binding energy values with respect to 3ert protein. Some of the compounds exhibited excellent activity against MCF-7 cancer cell line and studied molecular interaction of probable target protein, human estrogen receptor alpha protein (3ert.pdb) using docking simulation.